PETA KORUPSI DI KABUPATEN KUDUS (studi kasus korupsi bupati kudus tahun 2019) - Dimas Rahmatullah; Krishno Hadi (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2022)
The crime of corruption is a crime that has a wide impact, in Indonesia itself there have been many cases of corruption that have occurred and it seems that it has become a culture for government officials. This study aims to create a corruption map by Muhammad Tamzil (Bupati Kudus period 2018 to 2023). This research uses a case study research method of content analysis on the Supreme Court's decision, data analysis using Nvivo12plus with data presentation in the form of graphs and tables. The results of the study revealed that the criminal acts of corruption committed by Muhammad Tamzil were in the form of gratification for the appointment of several parties and also receiving gifts from several inaugurated employees. Transactional becomes the highest action because in this case it involves many people and also the stages of the process are gradual. In every crime there is a correlation with each other, the 3 highest correlations are transactional and gratification with 0.982908 points. Transactional and bribes which have 0.949911 points, bribes and gratuities which have 0.949741 points. This research is expected to provide information to the public about what are the factors that cause corruption. The limitation of this research is that the data used is still limited to the type of secondary data, namely the Supreme Court decision document. The next research needs to use primary data, namely interview and observation data.